Evaluation of Gingival Inflammation, Plasma IL-6, and TMJ Clicking after Masseters Muscle Botulinum Toxin Injection and Intra-Articular PRP Injection In Bruxism Patients - Ali Sahib Hussein; Muhassad H. Al-Mudhafar; Karar Abdulzahra Mahdi; Ali A. Al-Fahham (Indian Journal of Forensic Medicine & Toxicology, 2021)
In this study, thirty patients complaining of bruxism at night and hyperactivity masseters muscle causing TMJdisk changes, TMJ clicking sound and all selected patient complaining of gingival inflammation as includedcriteria, and 50-unit botulinum toxin type A were injected in both side of masseter muscle. Regarding toT.M.J clicking sound there were three intervals of PRP injection for 3 months. The levels of IL-6 in theblood samples measured by ELISA technique, this study proposed to investigate the plasma IL-6 level inpatient with early changes of T.M.J disorder and role of repetitive intraarticular PRP injection on the T.M.Jclicking sound and the effect of decreasing stress force microtruma of masseter muscle on gingival score inpreviously diagnosed bruxism patient with gingival inflammation whether of causative factor of gingivitis.The mean difference of plasma IL-6 in between patient and control (25.6 ± 4.2 and 23.8 ± 1.8) respectively.There were highly significant differences in gingival index score of all sided of oral cavity after botoxintramuscular injection. Force stress muscle microtruma of bruxism patient considered a contributory factorthat increased gingival inflammation these fact suggested by botulinum toxin injection to decrease this force,and highly statically difference on gingival score after injection and also, the intraarticular injection of PRPin T.M.J disorder patient statically not affected on the clicking sound of joint as well as suggesting in ourresearch for further studies to appear the role of IL-6 in early joint changes locally as an experimental study